The role of m6A demethylases in lung cancer: diagnostic and therapeutic implications - Yu, Mengjiao; Ji, Wenqian; Yang, Xu; Tian, Kai; Ma, Xinyi; Yu, Shali; Chen, Lin; Zhao, Xinyuan (Frontiers in Immunology, 2023)
m6A is the most prevalent internal modification of eukaryotic mRNA, and plays a crucial role in tumorigenesis and various other biological processes. Lung cancer is a common primary malignant tumor of the lungs, which involves multiple factors in its occurrence and progression. Currently, only the demethylases FTO and ALKBH5 have been identified as associated with m6A modification. These demethylases play a crucial role in regulating the growth and invasion of lung cancer cells by removing methyl groups, thereby influencing stability and translation efficiency of mRNA. Furthermore, they participate in essential biological signaling pathways, making them potential targets for intervention in lung cancer treatment. Here we provides an overview of the involvement of m6A demethylase in lung cancer, as well as their potential application in the diagnosis, prognosis and treatment of the disease.